2007
DOI: 10.1088/0143-0807/28/5/022
|View full text |Cite
|
Sign up to set email alerts
|

The elastic body model: a pedagogical approach integrating real time measurements and modelling activities

Abstract: In this paper, we describe a pedagogical approach to elastic body movement based on measurements of the contact times between a metallic rod and small bodies colliding with it and on modelling of the experimental results by using a microcomputer-based laboratory and simulation tools. The experiments and modelling activities have been built in the context of the laboratory of mechanical wave propagation of the two-year graduate teacher education programme of Palermo's University. Some considerations about obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…However, our multimethod analysis can supply hints for the effective design and development of a learning environment aimed at improving students' abilities in using explicative models. In fact, our data highlight the need for our students to better identify differences and similarities between descriptive and explicative procedures, as well as the way these are related to understanding reality [59,[83][84][85][86]. This could help students to get some aspects of the world at the level of causation and mechanisms of functioning [23], by orientating them towards broader generalizations involved in theory construction.…”
Section: Conclusion and Implication For Teachingmentioning
confidence: 89%
“…However, our multimethod analysis can supply hints for the effective design and development of a learning environment aimed at improving students' abilities in using explicative models. In fact, our data highlight the need for our students to better identify differences and similarities between descriptive and explicative procedures, as well as the way these are related to understanding reality [59,[83][84][85][86]. This could help students to get some aspects of the world at the level of causation and mechanisms of functioning [23], by orientating them towards broader generalizations involved in theory construction.…”
Section: Conclusion and Implication For Teachingmentioning
confidence: 89%
“…A complete analysis of the dynamics of the collision is described elsewhere [6,8]. In short, it is found that m br and m al represent the mass values such that colliding bodies completely come to rest after the collision with brass and aluminium rods (of 1 cm cross-section diameter), respectively 3 .…”
Section: Discussionmentioning
confidence: 99%
“…These methods are mainly based on the generation of wave pulses in metallic rods by means of collisions of a metallic body at one of the rods' ends and on the measurement of the time the waves take to travel along the rods. In another paper [6], some experimental aspects regarding the mechanisms of wave propagation in solids have been analysed and a simple model, aimed at figuring out the experimental results, was built and implemented by using the interactive physics (IP) pedagogical simulation environment 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Research also highlighted the need for the students to better identify differences and similarities between descriptive and explicative procedures and models, as well as the way these are related to understanding reality and perceiving science (Sperandeo-Mineo et al, 2006;Duit et al, 2005;Fazio et al, 2007;Tarantino et al, 2010). As it is well known, in the process of construction of explicative models inductive reasoning is involved, but an important role is also played by analogical reasoning .…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%